Persepsi masyarakat tentang hukum syariah menabung di Bank dan tingkat literasi keuangan syariah - Atep Hendang Waluya (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study has three objectives. First, to find out the people of Tangerang City perception aboutsharia law regarding saving in Islamic and conventional banks. Second, to find out their Islamicfinancial literacy level. And third, to determine the relationship between their perceptions and theirIslamic financial literacy level. This study uses quantitative methods with primary data collectedby integrating questionnaires in 13 sub-districts in the city of Tangerang. The method used todetermine the number of samples is the Slovin formula, while data analysis uses the Kendall’sTau correlation. This study produced several findings. First, the perception of the Tangerang citypeople about the law of saving in Islamic banks is dominated by the answer recommended, whilethe saving law in conventional banks according to the majority of the people of Tangerang City ispermissible. Second, the level of sharia financial literacy in Tangerang City is low, with the lowestindicators are their skills in using Islamic financial services. Third, there is a strong relationshipbetween the people of Tangerang City perception about sharia law saving in banks with the levelof Islamic financial literacy.